Komposisi Bahasa Melayu Palembang: Sebuah Kajian Morfologis - Andina Muchti (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
The purpose of this study was to describe the form and meaning of the Palembang Malay composition. The object of research is focused on the morphological process in Palembang Malay, namely on the form and meaning of the composition. The research method used is the distributional method. The data were obtained by means of observation and documentation, namely documenting the Palembang Malay which was sourced from the Palembang language dictionary. The composition is based on the relationship of the supporting elements, namely a combination of words for words and a combination of main words and main words. From the results, there are two forms of composition in Palembang Malay, namely (1) a compound form whose first element becomes the center/explained (D) by an explanatory element (M) and (2) a compound form whose elements do not explain each other, but only a series of parallel or copulative. The meaning of the Palembang Malay composition does not depend on the meaning of the elements that make it up because the composition forms a new meaning that is not the same as the original meaning. There are five meanings arising from the compositional process in Palembang Malay, namely dregs/feces, biological family, condition, characteristics, and meaningful composition of tools. In contrast to previous studies, there are two meanings arising from the composition process of the Palembang Malay language, namely the meaning of process and state.